Paradigm of Buddhist peace in different thinking society - phunthawong, Prasit; Thongchuay, Natthita; Suwannual, Patchlada (Journal of International Buddhist Studies, 2017)
This article aims to study the crystallized science and art of paradigm of Buddhist peace in the different thinking society to solve the root causes of conflict, building harmony and realizing the duty together happily as a guideline for development with the paradigm in developing the country as the starting point in driving the country towards stability, prosperous and sustainability of current government. It is the light that makes Thailand be free from “trap of the conflict” into a “harmony of the nation” a peaceful society to live and full of smiles in the future.